Caracterização química e atividade antiulcerogênica gástrica dos polissacarídeos obtidos da cultura de calos de Cereus peruvianus Mill. (CACTACEAE) - Jayme, Milena de Oliveira (2013)
The cactus "Mandacaru", Cereus peruvianus Mill. (Cactaceae) has many applications with economic and industrial interest. The culture of callus of C. peruvianus is an alternative source for the synthesis of products originally produced by plants. We now report isolation procedure, characterization and structural analysis of polysaccharides from callus culture of C. peruvianus and determination of its antiulcerogenic effect. The polysaccharide obtained was dialyzed and subjected to freeze-thaw process, providing PAG polysaccharide consisting of galactose, arabinose, uronic acid and xylose in the ratio of 71:15:9:5, besides traces of rhamnose. This profile of monosaccharide composition suggests that the polysaccharide may be an arabinogalactan, such as that found in the plant originally.This appeared heterogeneous when analyzed by HPSECMALLS. The polysaccharide PAG showed significant antiulcerogenic activity in ethanol-induced model suggesting that the gastroprotective effect of this arabinogalactan is due to the ability of these polymers adhere to the surface of the gastric mucosa, acting as an effective barrier inhibiting mucosal erosions.